A Novel Tool to Guide Reintegration of Anesthesiologists Into Clinical and Academic Work After Concussion. Issue 9 (1st May 2019) - Hatton, Kevin W.; Bacon, J. David; McKinney, Katherine; Schell, Randall M.
Abstract : Concussion is a common form of mild traumatic brain injury that can cause somatic, cognitive, and behavioral impairments lasting days to weeks. There are no published guidelines or recommendations to facilitate the safe and successful reintegration of anesthesiologist clinicians and trainees into clinical and academic work after concussion. We developed a simple 4-phase postconcussion recovery protocol for anesthesiologists who have suffered concussion and describe the successful use of this postconcussion recovery protocol to support reintegration of an Anesthesiology Critical Care Medicine fellow who developed mild concussion during vacation leave.